Incidence and patterns of pediatric fractures at selected hospitals in Addis Ababa, Ethiopia, 2024: a multi-center cross-sectional study - Muzemil, Sefa; Mekasha, Amha; Muzemil, Fetiha; Barega, Muhiddin Tadesse; Eanga, Shamill (Frontiers in Pediatrics, 2025)
IntroductionNearly 2,000 children under the age of 14 die every day due to injuries, with fractures accounting for 10%–25% of these cases. The burden of pediatric fractures is significant, but neglected and many can be prevented through simple and cost-effective community-level interventions. However, no studies have been conducted in our country regarding the incidence and patterns of pediatric fractures. Without comprehensive data, it is challenging to set priorities, formulate policies, and implement preventive measures. Therefore, this study aims to determine the incidence and patterns of pediatric fractures at selected hospitals in Addis Ababa in 2024.Materials and methodsA multi-center cross-sectional study was conducted from October 10, 2023, to February 15, 2024, in the emergency unit and pediatrics ward of three public hospitals in Addis Ababa, Ethiopia: Tikur Anbesa Specialized Hospital (TASH), Yekatit 12 Hospital, and Alert Hospital. Data was collected by bachelor's degree nurses using an interviewer-administered structured questionnaire. Data was refined, coded, and entered into Epi Info version 7 computer software, then exported into SPSS version 21 for data cleaning and analysis.ResultsFrom a total of 648 children who encountered trauma, 182 cases were fractures, resulting in an incidence of 28% (95% CI: 26.5–29.7). The major patterns of injury were due to falls (79%), road traffic accidents (RTAs) (15.4%), and assaults (5.6%). The upper limb was the most common site of injury (73%). Fifty-four percent of the children had injuries to two structures.ConclusionsThe overall incidence of pediatric fractures among those who encountered trauma was 28%. Male children exhibited a higher incidence of fractures than female children. The highest risk of fractures occurred in children aged 6–10 years. Upper limb fractures were observed more frequently than lower limb fractures.